Discovering Messages in COVID-19 Advertisements: A Semiotic Analysis - Adik Mariani, Ni Putu; Eka Pratiwi, Desak Putu; Juniarta, I Wayan (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2021)
COVID-19 advertisement is a kind of advertisement which used to convey the information about COVID-19 as well as instructions regarding to health protocols to avoid us from the danger of COVID-19. This study concerned on finding out the messages carried by both verbal and nonverbal signs in COVID-19 advertisements. The data were taken from Pinterest. The data were collected by observation method.  The collected data were analyzed by qualitative method using theory of semiotics from Saussure (1983), the theory of meaning from Barthes (1977), and theory of color term from Wierzbicka (1996). The message is presented in formal and informal way. Our findings show that verbal and nonverbal cues in advertisements generally convey the messages that during the pandemic people have to obey protocols such as staying at home, wearing masks correctly, keep social distancing, and washing hands.